THE EFFECTS OF LEPTIN ADMINISTRATION ON RENAL FUNCTION IN SPONTANEOUSLY HYPERTENSIVE RATS - Caszo, Brinnell; Muslim, Azdayanti; Awang, Zanariah; Omar, Effat; Ibrahim, Effendi; Singh, Harbindarjeet (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Elevated levels of leptin may be responsible directly for progression and severity of renal disease in obesity and hypertension. It may exert its effects by promoting fibrosis through the actions of transforming growth factor-Î²1 (TGF-Î²1) and the Smad pathway. This study determines the effect of leptin administration on the development of renal fibrosis in nonobese spontaneously hypertensive rats (SHRs). Methods: Male SHRs, aged 12-14 weeks, were injected with either leptin (60 Âµg/kg/day) or saline (for the control group) subcutaneously daily for 42 days. At the end of the experimental period, animals were euthanized and their kidneys were removed. The right kidney was harvested for the determination of messenger ribonucleic acid (mRNA) expression of TGF-Î²1, Smad2, Smad3, and bone morphogenic protein 7 (BMP7). The left kidneys were stored in neutral buffered 10% formalin until they were processed and stained with hematoxylin and eosin. Prepared slides were examined under light microscopy. 30 consecutive glomeruli were examined for the cell counts based on the number of nuclei seen and the total area of glomeruli. Results: No significant difference was evident in renal function between control and leptin-treated rats. Cellularity and area of glomeruli were also not different between the two groups. mRNA expression of TGF-Î²1, Smad2, and BMP7 were, however, higher in leptin-treated rats. Conclusion: It appears that 6 weeks of leptin administration increases renal TGF-Î²1 and Smad2 levels but with little morphological changes in the kidney. Whether the elevated BMP7 expression was responsible for lack of effect of leptin on renal morphological changes remains unclear. Keywords: Leptin, Renal function, Hypertension, Glomerulus, Transforming growth factor-Î²1, Smad, Spontaneously hypertensive rats.